Some Seed Fell on Good Ground : The Life of Edwin V. O'Hara - Dolan, Timothy Michael (Book collections on Project MUSE., 2012)
A historical biography that "illuminates a remarkable churchman who was in the vanguard of his time," written by New York's archbishop (Publishers Weekly). A man far ahead of his time, Archbishop Edwin V. O'Hara of Kansas City (1881'1956) orchestrated numerous initiatives that profoundly affected American Catholic life. His ceaseless activity as both priest and bishop sowed seeds that flourished long past his lifetime, from liturgical reform to Bible study, campus ministry to social justice, minimum wage legislation to founding the National Catholic Rural Life Conference. The pastoral challenges he confronted in the first half of the last century'institutional complacency; disorganization among Catholics and reluctance to openly profess their faith; ignorance of social justice principles; the defense of the Church in a sometimes hostile culture'all remain significant challenges for the American Church today. Timothy Michael Dolan, Archbishop of New York, researched and composed this biography and continues to cite O'Hara as his role model of an immensely effective bishop. In an effort to revisit the pioneering work of church leaders, this book includes a new preface by Archbishop Dolan. "This is the long-needed definitive life of one of the American Church's greatest leaders." 'The Catholic Key.